Ethnic Heritage in Mississippi : The Twentieth Century - Carpenter, Barbara; Walton, Shana, 1961- (Book collections on Project MUSE., 2012)
Throughout its history, Mississippi has seen a small, steady stream of immigrants, and those identities--sometimes submerged, sometimes hidden--have helped shape the state in important ways. Amid renewed interest in identity, the Mississippi Humanities Council has commissioned a companion volume to its earlier book that studied ethnicity in the state from the period 1500-1900. This new book, Ethnic Heritage in Mississippi: The Twentieth Century, offers stories of immigrants overcoming obstacles, immigrants newly arrived, and long-settled groups witnessing a revitalized claim to membership. The book examines twentieth-century immigration trends, explores the reemergence of ethnic identity, and undertakes case studies of current ethnic groups. Some of the groups featured in the volume include Chinese, Latino, Lebanese, Jewish, Filipino, South Asian, and Vietnamese communities. The book also examines Biloxi as a city that has long attracted a diverse population and takes a look at the growth in identity affiliation among people of European descent. The book is funded in part by a "We the People" grant from the National Endowment for the Humanities